KREATIVITAS GURU DALAM PENGGUNAAN MEDIA YOUTUBE PADA PEMBELAJARAN PAI DI KELAS V SD NEGERI 100790 SITUMBAGA KABUPATEN PADANG LAWAS UTARA - Eva Khoirunnisa; Charles Charles (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. This research is motivated by the low creativity of teachers today. This is seen from the reality in the field. This study aims to find out how the teacher's creativity in using YouTube media in PAI learning at SDN 100790 Situmbaga, North Padang Lawas district. This research is a research using qualitative research methods with a phenomenological approach. Collecting data through observation, interviews, and documentation. The data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of the study show that the teacher's creativity in creating new ideas is only developing videos from YouTube, and in developing new concepts is by making videos or learning content and when finding something new is looking for references from other accounts and in producing something new it can make students understand more about learning and the obstacles faced by teachers are the lack of learning infrastructure in schools, such as laptops, frequent power outages, making the network slower.